Effects of zinc on bovine mammary epithelia - Shaffer, James (Kansas State University, 2016)
Two experiments were conducted to explore potential cellular and biochemical mechanisms by which zinc may impact milk production and mammary health of dairy cattle. For the first experiment, twelve lactating Holstein cows were enrolled in a replicated 3 x 3 Latin square, and provided a balanced diet supplemented with either 30 ppm zinc as ZnSO₄ (30-ZS), 60 ppm zinc as ZnSO₄ (60-ZS), or 60 ppm zinc as a mixture of ZnSO₄ and Zn methionine (60-ZM). Blood and milk were collected and analyzed for markers of blood-milk leak and dairy food properties of milk. Milk cells were also isolated and analyzed for RNA abundance of genes related to zinc-mediated apoptosis. Aside from a tendency for 60-ZS to increase feed intake and 60-ZM to increase milk fat compared to 30-ZS, no effects were observed on performance, markers of blood-milk leak, transcript abundance of selected genes, or dairy food properties of milk. A cell culture study was also conducted using immortalized bovine mammary epithelial (MAC-T) cells. Messenger RNA abundance of GPR39—a G protein-coupled receptor shown to regulate cellular activity in response to extracellular zinc concentrations in other epithelial cell lines—was knocked down using RNA interference. Following GPR39 knockdown, cells were treated with 0 or 100 μM zinc. Phosphorylation of the kinases ERK1/2 and AKT was measured in GPR39-knockdown and control cells treated with either 0 or 100 μM zinc. No effect of zinc treatment or GPR39 knockdown was detected on kinase phosphorylation. Interestingly, the 100 μM zinc treatment showed a tendency to increase GPR39 mRNA abundance in control cells. There remain many questions about the cellular mechanisms whereby zinc can impact milk production in dairy cattle.
Keywords: Mammary epithelia; Zinc; Ruminant nutrition; Dairy